PROBLEMATIKA PERMOHONAN GRASI MENURUT UNDANG-UNDANG NOMOR 22 TAHUN 2002 - Niken Subekti Budi Utami (Fakultas Hukum Universitas Gadjah Mada, 2008)
According to executor attorney opinion, no time limit for application clemency, it wills be performing deep constraint on dead punishment execution. Execution of dead punishment also constraint by rule that allows criminal to propose the second clemency application. This constraint still is added by condition that second clemency application is two years of first clemency rejection. Meanwhile according to criminal lawyer reception, with no rule upon, constitute a advantage by criminal dead, since it can propose clemency without time limit for first clemency application and also second application, so execution could be delayed. At Yogyakarta court since year 2002 until now there is no criminal propose clemencies. It is caused, firstly, certain verdict type that could be requested for clemency, secondary by apply clemency cause dead sentence is no postpone except for dead verdict, thirdly most criminal on narcotic and drug abuse case was pleased with first grade verdict.